69-6x=21x+21

Simple and best practice solution for 69-6x=21x+21 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 69-6x=21x+21 equation:


Simplifying
69 + -6x = 21x + 21

Reorder the terms:
69 + -6x = 21 + 21x

Solving
69 + -6x = 21 + 21x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-21x' to each side of the equation.
69 + -6x + -21x = 21 + 21x + -21x

Combine like terms: -6x + -21x = -27x
69 + -27x = 21 + 21x + -21x

Combine like terms: 21x + -21x = 0
69 + -27x = 21 + 0
69 + -27x = 21

Add '-69' to each side of the equation.
69 + -69 + -27x = 21 + -69

Combine like terms: 69 + -69 = 0
0 + -27x = 21 + -69
-27x = 21 + -69

Combine like terms: 21 + -69 = -48
-27x = -48

Divide each side by '-27'.
x = 1.777777778

Simplifying
x = 1.777777778

See similar equations:

| 8/7w=56 | | 13-(5m+4)=5+3m-12 | | 5+x/4=11 | | 9+8x-3=2(3x+8) | | 5h+7=5(h+2)-3 | | X(8x+11)=6x-5 | | X+5/6=-1/5 | | (4/15)-(1/6) | | Y=6*-2+6 | | 0.7/14 | | 2=9+x/7 | | 6/x+5=-15/x-2 | | 14/0.7 | | (x^7/4)-(4x^7/8)+4=0 | | x-115=125 | | z-2323233322=-23-2z | | log(5+r)=log(5s-2) | | x+23+3x=-11-3x-15 | | 2(m-1)=-4 | | 9+8-3=2(3+8) | | x^7/4-4x^7/8+4=0 | | 3-(1/6)x=(7/3) | | 3.2(x-1.6)=5.88+0.2x | | 6/x-1=-36/x-8 | | 2*2*2*2*2*2= | | 9e-4(3+2e)= | | tanX=3 | | -1/2y=-4 | | -102=17k | | -2(u-1)=-5u+5 | | -4(x+7)=52 | | 4/x-5=-48/x+8 |

Equations solver categories